Keterampilan Passing Bawah Bola Voli: Apakah Terdapat Hubungan Dengan Koordinasi Mata Tangan Dan Keseimbangan - M. Zikrillah; Merlinasar Merlinasar (Journal on Education, 2024)
The aim of this research is to determine the relationship between hand-eye coordination and balance on volleyball passing skills at SMP Negeri 2 Cerenti, Kuantan Singingi Regency. This type of research is correlation. The population of this study was students of SMP Negeri 2 Cerenti, Kuantan Singingi Regency, totaling 18 male students. The sampling technique is total sampling so that the sample in this study was 18 people. The research instruments used were a hand-eye coordination test, a balance test and a volleyball underpass test. Based on the research results, the conclusions obtained in this research are: (1) There is a relationship between hand-eye coordination and volleyball passing skills of students at SMP Negeri 2 Cerenti, Kuantan Singingi Regency with a calculated r value = 0.595 > r table = 0.468, (2) There is a relationship balance towards volleyball underpassing skills of students at SMP Negeri 2 Cerenti, Kuantan Singingi Regency with a calculated value of r = 0.589 > r table = 0.468, (3) There is a relationship between eye-hand coordination and balance towards volleyball underpassing skills for students at SMP Negeri 2 Cerenti, Kuantan Singingi Regency with calculated r value = 0.595 > r table = 0.468.